Familial hypercholesterolaemia: cholesterol efflux and coronary disease. (20th June 2016) - Versmissen, Jorie; Vongpromek, Ranitha; Yahya, Reyhana; van der Net, Jeroen B.; van Vark‐van der Zee, Leonie; Blommesteijn‐Touw, Jeannette; Wattimena, Darcos; Rietveld, Trinet; Pullinger, Clive R.; Christoffersen, Christina; Dahlbäck, Björn; Kane, John P.; et al.
Abstract: Background: Coronary heart disease (CHD) risk inversely associates with levels of high‐density lipoprotein cholesterol (HDL‐C). The protective effect of HDL is thought to depend on its functionality, such as its ability to induce cholesterol efflux. Materials and methods: We compared plasma cholesterol efflux capacity between male familial hypercholesterolaemia (FH) patients with and without CHD relative to their non‐FH brothers, and examined HDL constituents including sphingosine‐1‐phosphate (S1P) and its carrier apolipoprotein M (apoM). Results: Seven FH patients were asymptomatic and six had experienced a cardiac event at a mean age of 39 years. Compared to their non‐FH brothers, cholesterol efflux from macrophages to plasma from the FH patients without CHD was 16 ± 22% (mean ± SD) higher and to plasma from the FH patients with CHD was 7 ± 8% lower ( P = 0·03, CHD vs. non‐CHD). Compared to their non‐FH brothers, FH patients without CHD displayed significantly higher levels of HDL‐cholesterol, HDL‐S1P and apoM, while FH patients with CHD displayed lower levels than their non‐FH brothers. Conclusions: A higher plasma cholesterol efflux capacity and higher S1P and apoM content of HDL in asymptomatic FH patients may play a role in their apparent protection from premature CHD.